Online Arabic Education Model During the Covid-19 Pandemic: نموذج تعليم اللغة العربية عبر الإنترنيت في جائحة كوفيد-١٩ - Maskud Maskud; Rifki Yoga Pratama (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2021)
The delivery of technology and information presents the educational model. Teachers are considered an effective model of teaching Arabic using sophisticated technology and information. In addition to considering the covid-19 epidemic that impacts the educational process, the online education model becomes an effective way for students to learn undefined. The approach used in this study is qualitative in descriptive studies because the data that researchers need is a description of the data and detailed information about the incoming content. This method describes what is happening according to facts and field results. The results of this study are as follows: 1) steps of teaching Arabic through the Internet 2) planning of language teaching through the Internet 3) Implementation of Arabic teaching through the Internet 4) evaluation of Arabic teaching through the Internet. تقدم نوذج التعليم متمرا وفقا لتقديم التكنولوجيا والمعلومات. ولذلك، يعد المعلم نوذج تعليم اللغة العربية الفعال بايتخدام التكنلوجيا والمعلومات المتطورة، وبالإضافة الى النظر هذا وباء كوفيد-19 الذي كان له تأثير بعملية التعليم، نموذج التعليم عبر الإنترنيت أصبحت وسيلة فعالة للتلاميذ في التعلم غير محدد. إن المدخل المستعمل لهذا البحث هو الكيفي على دراسات وصفية، لأن البيانات التي يحتاج اليها الباحث تكون صورة المعلومات البيانات والتفصيلية عن مضمون المدخل. أن هذه الطريقة تهدف الى وصف ما حدث وفق حقائق ونتائج المجال. ونتائج هذا البحث مايلي : 1) خطوات تعليم اللغة العربية عبر الإنترنيت 2) تخطيط تعليم اللغة عبر الإنترنيت 3) تنفيذ تعليم اللغة العربية عبر الإنترنيت 4) تقييم تعليم اللغة العربية عبر الإنترنيت.